PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, NIAT MEMBAYAR PAJAK, DAN LINGKUNGAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK HOTEL DAN RESTORAN - I Kadek Litawan; I Putu Nuratama (Hita Akuntansi dan Keuangan, 2021)
This study aims to examinegthegeffectgofgmodernizationgof the tax administration system, the intention to pay taxes, and the taxpayer's environmentgonghotelgand restaurant taxpayer compliance (empirical study on hotels and restaurants in Bangli Regency). The population used in this study were all hotels and restaurants registered in the Regional Finance, Revenue and Asset Agency (BKPAD) Bangli Regency as many as 39 hotels and restaurants. Determination of the sample using purposive sampling in order to obtain 39 people as the sample. After the instrument test and classical assumption test were carried out, the data analysis was then carried out using multiple linear regression analysis, determination, t test, and F test. The analysis showed that the effect of modernization of the tax administration system on taxpayer compliance obtained a regressiongcoefficientgofg0.305,gthegtgvalue.gcountgofg2.793gand the significant value of the t test of 0.008 <0.05, so that H1 is accepted. The effect of the intention togpaygtaxesgongtaxpayergcompliancegobtainedga regression coefficient of 0.402,gthegtgvaluegofg3.214gand a significantgvaluegofgthegtgtestgofg0.003g<0.05, so that H2 is accepted. The influence of the taxpayer environment on taxpayer compliance obtained a regression coefficient of 0.327, the tgvaluegofg2.260gandgagsignificantgvalue ofgthegtgtestgofg0.030g<0.05,gsogthatgH3gisgaccepted. It is suggested to Hotels and Restaurants in Bangli Regency to jointly encourage the surrounding community and other hotels and restaurants to comply with paying taxes so that they can jointly remind each other of taxpayer compliance.